Reinforced masonry practical booklet: A discussion of the architectural production of the contemporary city and the social and cultural sus-tainability of Latin American architecture. - Albuquerque, Caio Coelho Silva; Moura, Célio Henrique Rocha; Araujo, Felipe Moura Hemetério (National Journal of City Management, 2021)
The main work explains the elaboration process of a didactic booklet that details the constructive method of reinforced masonry, final product of an investigation developed by the department of Architecture and Urbanism at Universidade Federal de Pernambuco (UFPE), entitled “Alvenaria Cerâmica Armada: uma cartilha prática”[1], at 2020. This article presents a discussion concerning urban sustainability, here understood not from it ecological dimension only, but also from it’s social and cultural. The post-modern Productivism from the 70’s decades impulses an architectural production which impacts the landscape and life quality of city’s population, presenting a homogenization in what concerns architecture. Contrasting this universalized architectural movement, some notably Latin-American architectural offices, using materials and local techniques, started to answer the local demands (and international) under the sustainable directive, intending to use low cost and using resources and rejects from local site to build. Based on the practical experience at one of these offices, the Paraguayan office Gabinete de Arquitectura, it was possible to elaborate a guidebook synthesizing some precepts and building techniques in reinforced masonry, a method easily reached by the most popular layers of society. By this guidebook it is uncovered many possibilities for an architectural low cost production with both social and cultural commitments. [1] Reinforced Masonry Practical Booklet.